2002
DOI: 10.1046/j.0953-816x.2001.01874.x
|View full text |Cite
|
Sign up to set email alerts
|

Speech listening specifically modulates the excitability of tongue muscles: a TMS study

Abstract: The precise neural mechanisms underlying speech perception are still to a large extent unknown. The most accepted view is that speech perception depends on auditory-cognitive mechanisms speci®cally devoted to the analysis of speech sounds. An alternative view is that, crucial for speech perception, it is the activation of the articulatory (motor) gestures that generate these sounds. The listener understands the speaker when his/her articulatory gestures are activated (motor theory of speech perception). Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
517
5
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 732 publications
(570 citation statements)
references
References 20 publications
41
517
5
7
Order By: Relevance
“…In addition to the well-known fact that speech production is tightly related to the motor cortex, some studies have shown that the motor cortex is activated in speech perception tasks [24][25][26][27][28][29][30] . For example, when listeners [26,27] , suggesting that different speech stimuli activate motor cortical regions with different patterns.…”
Section: Anatomical and Functional Associations Between The Auditory mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the well-known fact that speech production is tightly related to the motor cortex, some studies have shown that the motor cortex is activated in speech perception tasks [24][25][26][27][28][29][30] . For example, when listeners [26,27] , suggesting that different speech stimuli activate motor cortical regions with different patterns.…”
Section: Anatomical and Functional Associations Between The Auditory mentioning
confidence: 99%
“…For example, when listeners [26,27] , suggesting that different speech stimuli activate motor cortical regions with different patterns. In other words, listening to various verbal stimuli may cause differential automatic activations of cortical regions involved in speech production.…”
Section: Anatomical and Functional Associations Between The Auditory mentioning
confidence: 99%
“…For example, goal representations have a crucial role in the planning and control of action, and action understanding and imitation are performed at the goal rather than at the movement level (Iacoboni et al, 2005;Wohlschläger, Gattis,& Bekkering, 2003). Moreover, it has been shown that these apparently unrelated abilities and others which were believed to be in the realm of abstract thought, such as language understanding, share common representational structures and mechanisms in the brain and involve signiWcant use of the motor system (Fadiga, Craighero, Buccino, & Rizzolatti, 2002;Pulvermüller, 1999). Recent studies have revealed the crucial role of canonical and mirror neurons (Rizzolatti & Craighero, 2004;Rizzolatti et al, 1988) and internal forward models (Kawato, 1999;Wolpert & Ghahramani, 2004) in most of the aforementioned tasks.…”
mentioning
confidence: 99%
“…Because in typical language development speech production leads to auditory perception of the self-produced sounds, Hebbian learning entails a coupling of specific motor and auditory circuits in distributed sensorimotor circuits (Fry, 1966;Pulvermüller & Preissl, 1991;Pulvermüller, 1999). The presence in the cortex of strong links associating speech sounds with corresponding articulations has been confirmed by a significant body of experimental evidence (Pulvermüller, 1999;Fadiga et al, 2002;Wilson et al, 2004;Pulvermüller & Fadiga, 2010). Therefore, the model of the auditory cortex used in Experiment 1 was extended here by adding three areas ( Fig.…”
Section: Experiments 2 -Long-term Memory Mmn In the Language Cortexmentioning
confidence: 97%
“…However, the ability to learn and later recognise and distinguish large numbers of input patterns, including scenes, specific faces, sounds, and words, requires mechanisms for learning and storage of long-term memory (LTM) traces. Whereas the former (changedetection) capacity is shared by a range of animals, the acquisition of large "vocabularies" is limited to a set of higher vertebrates, and is believed to have played a crucial role in the evolutionary advantage of mammals (Pulvermüller, 1999;Fadiga et al, 2002;Wilson et al, 2004;Fagot & Cook, 2006;Voss, 2009;Pulvermüller & Fadiga, 2010). LTM traces, after having formed, act as long-term representations for patterns of sensory input, i.e., they can be re-activated, thereby signalling the presence of the corresponding elements in the environment.…”
Section: Introductionmentioning
confidence: 99%